Sungai Serayu dalam Tinjauan Sejarah Maritim: Peran dan Perkembangannya di Cilacap Pada Masa Hindia Belanda, 1830-1942 - Erlangga, Gery; Andi, Andi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2023)
The presence of rivers in human life has provided many benefits. One of the rivers that play a role in human life is the Serayu river in Central Java. So this study aims to analyze the origin, role and development of the Serayu river in Central Java, especially in the Cilacap region during the Dutch East Indies period. This research has a novelty in the study of the Serayu river in maritime history review. The method used in this study is a historical method consisting of four steps, namely heuristics, source criticism, interpretation and historiography. The results showed that the origin of the Serayu river originated from the migration process of the people of Kalimantan island to Java in the early century AD until it developed into a river that played a role in maritime activities such as shipping and trade in Cilacap during the Dutch East Indies. The conclusion of this study is that the Serayu river during the Dutch East Indies period (1830-1942) had a role and influence on the development of the Cilacap region as one of the centers of economic activity on the south coast of Java.Kehadiran sungai dalam kehidupan manusia telah memberikan banyak manfaat. Salah satu sungai yang turut berperan dalam kehidupan manusia adalah sungai Serayu di Jawa Tengah. Sehingga penelitian ini bertujuan untuk menganalisis asal-usul, peran dan perkembangan sungai Serayu di Jawa Tengah khususnya pada wilayah Cilacap pada masa Hindia Belanda. Penelitian ini memiliki kebaharuan dalam kajian sungai Serayu dalam tinjauan sejarah maritim. Metode yang digunakan dalam penelitian ini adalah metode historis yang terdiri dari empat langkah yakni heuristik, kritik sumber, interpretasi dan historiografi. Hasil penelitian menunjukan bahwa asal-usul sungai Serayu berawal dari proses migrasi penduduk pulau Kalimantan menuju Jawa pada awal abad masehi hingga berkembang menjadi sebuah sungai yang berperan dalam aktivitas kemaritiman seperti pelayaran dan perdagangan di Cilacap pada masa Hindia Belanda. Kesimpulan dari penelitian ini adalah sungai Serayu pada masa Hindia Belanda (1830-1942) memiliki peran dan pengaruhnya terhadap perkembangan wilayah Cilacap sebagai salah satu pusat dari aktivitas ekonomi di pesisir Selatan pantai Jawa.